Improving the benefits of HIV testing and referrals in large household surveys through active linkages to care: lessons and recommendations from the Namibia population-based HIV impact assessment (NAMPHIA), 2017. Issue 10 (3rd October 2021) - Grasso, Michael A.; Hamunime, Ndapewa; Maher, Andrew D.; Cockburn, David; Williams, Dan B.; Taffa, Negussie; Hong, Steven Y.; Jackson, Keisha; Wolkon, Adam; Low, Andrea; Stephens, Sally C.
ABSTRACT: In household-based surveys that include rapid HIV testing services (HTS), passive referral systems that give HIV-positive participants information about how and where to access ART but minimal follow-up support from survey staff may result in suboptimal linkage. In the 2017 Namibia Population-based HIV Impact Assessment (NAMPHIA), we piloted a system of active linkage to care and ART (ALCART) that utilized the infrastructure of existing community-based partner organizations (CBPOs). All HIV-positive participants age 15–64 years not on ART were given standard passive referrals to ART plus the option to participate in ALCART. Cases were assigned to CBPOs in participants' localities. Healthcare workers from the CBPO's contacted cases and facilitated their linkage to facility-based ART. A total of 510 participants were eligible and consented to ALCART. The majority were new diagnoses (80.8%), while the remainder were previously diagnosed but not on ART (19.2%). Of the 510, 473 (92.7%) were successfully linked into care. Of these, all but one initiated ART. Our ALCART system used existing CBPOs and contributed to >90% linkage-to-care and >99% ART-initiation among linked participants in a large, nationally-representative survey. This approach can be used to improve the potential benefits of HTS in other large population-based surveys.